Pengembangan Media Monopoli Berbasis Triprakoro Pada Pembelajaran Tematik di MI Al-Ittihad Jogoroto Jombang - Rafika Dwi Ismayati; Ali Mahsun (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2019)
Thematic learning is part of the 2013 curriculum which is being implemented as an educational system, which requires teachers to be creative and innovative in implementing the learning process so that media development is needed to attract students’ enthusiasm for learning in enhancing the overall understanding of thematic material. Based on this, in this study, researches developed Monochromatic Media (Triprakoro thematic material-based Monopoly) class IV Madrasah Ibtidaiyyah. The research method used is the R & D (Research & Development) Borg and Gall development model by adapting 8 steps namely potential and problems, data collection, product design, design validation, design revision, and trial use. Based on the development of monochromatic products, the validation results obtained are: validation of material experts got a score of 92% with very decent criteria, validation of learning design experts got a score of 92% with decent criteria, and validation of learning experts got a score of 92% with very decent criteria. Trial of product attractiveness based on assessment and student responses scored 88,7% with very interesting criteria. Thus it can be concluded that monochromatic media is effectively used in learning in madrasas.